STRATEGY SEGMENTING, TARGETING, DAN POSITIONING: STUDY ON PT SIDOMUNCUL - Rosyida, Afnani; Heriyani, Tian; Fuadi, Irfan; Dinia, Halifa (FEBI UIN Sunan Kalijaga, 2020)
Although promotion, production, distribution, and pricing are important indicators of marketing activities, many marketing efforts fail in carrying out their marketing strategies. A factor that often becomes a challenge in marketing is the lack of mastery of STP (segmentation, targeting, & positioning). This research uses secondary data. The secondary data needed comes from the 2019 financial statements obtained from the website of PT. Sido Appears Tbk. This study The purpose of this study was to analyze the strategic performance of market segments, targets and positions at PT. Sido Appears. Therefore, PT Sido Muncul has published its market not only for local but also international. PT Sido Muncul exports in Southeast Asia such as Malaysia, Vietnam, Myanmar and others. The company will also increase the distributor's ability to increase the consumer base in traditional and modern trade markets. From the 4P analysis, PT Sido Muncul did a close positioning with the Indonesian community and broad consumers in terms of promotions, prices, places and products.